a/ P(x)+Q(x) = \(4x^3+x^2-x+5+2^2+4x-1\)
= \(4x^3+x^2+3x+8\)
b/ P(x)-Q(x)= \(4x^3+x^2-x+5-2^2-4x+1\)
= \(4x^3+x^2-5x+2\)
a)
\(P\left(x\right)+Q\left(x\right)=\left(4x^3+x^2-x+5\right)+\left(x^2+4x-1\right)\)
\(=4x^3+x^2-x+5+x^2+4x-1\)
\(=4x^3+\left(x^2+x^2\right)+\left(-x+4x\right)+\left(5-1\right)\)
\(=4x^3+2x^2+3x+4\)
mik nghĩ bạn viết sai đề chỗ \(2^2\)
a)
\(P\left(x\right)+Q\left(x\right)=4x^3+x^2-x+5+2^2+4x-1=4x^3+x^2+3x+8\)
b)
\(P\left(x\right)-Q\left(x\right)=4x^3+x^2-x+5-2^2-4x+1=4x^3+x^2-5x+2\)